Efeito de Diferentes Níveis de Sódio e Fósforo sobre o Desempenho e a Qualidade da Casca dos Ovos de Poedeiras Comerciais - De Faria, Douglas Emygdio; Junqueira, Otto Mack [UNESP]; Sakomura, Nilva Kazue [UNESP]; Santana, Áureo Evangelista [UNESP] (My University, 2000)
An experiment was carried out to verify the effect of different levels of sodium and phosphorus (P) on the performance, eggshell quality and on some blood constituents of 144 laying hens Hy-Line W36, aged 60 weeks, allotted to 36 experimental units with four hens each. A randomized experimental block design was used in a factorial arrangement (3 × 3), sodium levels (.16, .20 and .24%) and phosphorus levels (.35, .45 and .55%), totalizing nine treatments, two blocks with two replicates each. The experimental diets were isoproteic (16.0% CP), isoenergetic (2,800 kcal ME/kg) and isocalcium (4.0% Ca). Feed intake, egg production, egg mass, feed:gain ratio, shell percentage, shell thickness and egg specific gravity were not affected by sodium levels. However, when the hens were fed diets containing .35% total P, there was impairment of the egg production, egg mass and feed:gain ratio, without modification of the eggshell quality characteristics. There was interaction between the factors for egg weight. Low phosphorus levels were not effective to improve the eggshell quality, but impaired hens performance.
Effect of Different Levels of Sodium and Phosphorus on Performance and Eggshell Quality of Laying Hens
Keywords: Eggshell quality; Laying hens; Nutrition; Phosphorus; Sodium